Epidural Volume Extension (EVE) - Sudadi; Mahmud; Wijaya, Indriyani (Jurnal Komplikasi Anestesi, 2021)
Epidural Volume Extension (EVE) technique injects normal saline into the epidural chamber immediately after the injection of local anesthesia into the intrathecal space. Normal saline injection will increase the epidural space thus increasing the spreading of local anesthesia in previous intrathecal injections and making the distribution of cerebrospinal fluid to be higher. It can be said that EVE technique utilizes the volume effect of normal saline that decreases the volume of intrathecal space. The EVE technique may be useful for reducing the dose of local anesthesia injected intrathecally by still reaching a stronger block height for surgery, as well as for faster recovery of motor blockades. Unfortunately, the EVE technique does not significantly reduce the risks of hypotension. Hypotension persists even though the hemodynamics change is more stable.